Teaching it to managers or teaching management to engineers? : None of the above - Navón, Jaime (2006)
Information Technology (IT) has been the greatest wealth generator of the last two decades and there is an increasing number of managers who see IT as a strategic weapon and want to harvest their profits. MBA programs are starting to incorporate IT but many times this component gets relegated to one or two irrelevant courses that nobody likes. The opposite direction of adding one or two courses of management to a typical IT program will not produce the future CEO that is needed. We present here our experience with a new program that takes the best of the two worlds. A balanced curriculum (50-50) can be made strong enough in management and in technology. The mixed background of students produces a rich environment where students with business backgrounds benefit from students with IT backgrounds and viceversa. The preliminary evaluation of this experience is very positive.